Swine influenza viruses in Northern Vietnam in 2013–2014 - Baudon, Eugénie (Emerg Microbes Infect, 2018)
Swine are an important intermediate host for emergence of pandemic influenza. Vietnam is the largest swine producer in South East Asia. Systematic virological and serological surveillance of swine influenza viruses was carried out in Northern Vietnam from May 2013 to June 2014 with monthly sampling of pigs in local and large collective slaughterhouses and in a live pig market. Influenza A seroprevalence in the local slaughterhouses and in the large collective slaughterhouse was 48.7% and 29.1%, respectively. Seventy-seven influenza A viruses were isolated, all from the large collective slaughterhouse. Genetic analysis revealed six virus genotypes including H1N1 2009 pandemic (H1N1pdm09) viruses, H1N2 with H1 of human origin, H3N2 and H1N1pdm09 reassortants, and triple-reassortant H3N2 viruses. Phylogenetic analysis of swine and human H1N1pdm09 viruses showed evidence of repeated spill-over from humans to swine rather than the establishment of H1N1pdm09 as long-term distinct lineage in swine. Surveillance at the large collective slaughterhouse proved to be the most efficient, cost-effective, and sustainable method of surveillance for swine influenza viruses in Vietnam.